PRE-COMPETITION PSYCHOLOGICAL STATE OF ATHLETES (PRE-COMPETITION PSYCHOLOGY) (International journal of artificial intelligence, 2026)
This article is devoted to the study of athletes' psychological state before competition, particularly pre-competition anxiety, emotional state, cognitive appraisal processes, and coping mechanisms. Pre-competition psychology is considered as a factor that directly affects athletic performance. Research findings indicate that moderate levels of anxiety, when properly managed, become facilitative by improving focus and increasing motivation, whereas excessive anxiety negatively impacts results. The article discusses types of anxiety, differences by gender and experience, the most effective psychological preparation methods, and practical recommendations for coaches.